Perbandingan Waktu Pencetakan dan Penggunaan Material pada Program Slicer 3d Print dengan Variasi Parameter Support Normal dan Tree - Muhammad Rizali; Ika Friscila (Pusat Riset dan Inovasi Nasional, 2024)
3D printing technology has revolutionized the way objects are designed and manufactured. One of the 3D printing methods is Fused Deposition Modeling (FDM). In the FDM process, thermoplastic filament is melted and extruded through a nozzle to build objects. An important aspect of FDM 3D printing is the use of support structures. Supports are necessary to support object parts that have overhangs or other complex geometries. There are two types of support structures, namely normal supports and tree supports. The selection of support type can affect printing time, material usage, and print quality. Slicer programs also play an important role in determining support parameters. This research aims to compare printing time and material usage on normal and tree support parameters with variations in slicer programs (Cura and Creality Slicer). This research uses a comparative experimental method. The independent variables in this research are support type (normal and tree), and the slicer programs used (Cura version 5.9 and Creality Slicer 6.0). The dependent variables in this research are printing time and material usage. In terms of print time, Creality software has a consistent print time, both for normal support and tree support. By comparing all parameters, Cura parameters with tree support can be selected, because it has the least material consumption, and a relatively short print time. The differences in time duration and material usage in 3D printing between different slicers are caused by the way each slicer processes 3D models and generates G-code for the printer. Each slicer uses different algorithms to calculate the extrusion path (toolpath) that the printer will follow. This affects the printing time and the amount of material used.